Faith in African Lived Christianity Bridging Anthropological and Theological Perspectives - Lauterbach, Karen; Vähäkangas, Mika (Global Pentecostal and Charismatic Studies, 2019)
Faith in African Lived Christianity brings together anthropology and theology in the study of how faith shapes the understanding of social life in Africa. It offers discussions on positionality, method, and political, social and ecological aspects of African Christian spirituality. Readership: The readership of this book consists of graduate and postgraduate students in African studies, social/cultural anthropology, ethnography, World Christianity, mission studies, theology and religion as well as researchers and teachers in these fields.